Impact of Organic Ligands on the Structure and Hydrogenation Performance of Colloidally Prepared Bimetallic PtSn Nanoparticles. Issue 7 (17th May 2013) - Altmann, Lena; Wang, Xiaodong; Stöver, Jörg; Klink, Miriam; Zielasek, Volkmar; Thiel, Karsten; Kolny‐Olesiak, Joanna; Al‐Shamery, Katharina; Borchert, Holger; Parisi, Jürgen; Bäumer, Marcus
Abstract The catalytic performance of ligand‐capped monometallic Pt and bimetallic PtSn nanoparticles supported on SiO2 toward the selective hydrogenation of acetylene to ethylene in ethylene‐rich streams was investigated. To evaluate the effect of organic ligands on the hydrogenation performance, dodecylamine (DDA)‐capped monometallic and bimetallic nanoparticles were compared with ligand‐free nanoparticles. Both ligands and Sn promote the selectivity of the catalysts. The most selective catalyst was found to be the DDA‐capped PtSn catalyst, with a nominal metal atom ratio of 1:1. An increase in Pt content resulted in a decrease in the selectivity, whereas an increase in Sn content caused a decrease in the activity.